Integrative transcriptomic analysis deciphering the role of rice bHLH transcription factor Os04g0301500 in mediating responses to biotic and abiotic stresses - Zhang, Qiuping; Teng, Rong; Yuan, Ziyi; Sheng, Song; Xiao, Yunhua; Deng, Huabing; Tang, Wenbang; Wang, Feng (Frontiers in Plant Science, 2023)
Understanding the signaling pathways activated in response to these combined stresses and their crosstalk is crucial to breeding crop varieties with dual or multiple tolerances. However, most studies to date have predominantly focused on individual stress factors, leaving a significant gap in understanding plant responses to combined biotic and abiotic stresses. The bHLH family plays a multifaceted regulatory role in plant response to both abiotic and biotic stresses. In order to comprehensively identify and analyze the bHLH gene family in rice, we identified putative OsbHLHs by multi-step homolog search, and phylogenic analysis, molecular weights, isoelectric points, conserved domain screening were processed using MEGAX version 10.2.6. Following, integrative transcriptome analysis using 6 RNA-seq data including Xoo infection, heat, and cold stress was processed. The results showed that 106 OsbHLHs were identified and clustered into 17 clades. Os04g0301500 and Os04g0489600 are potential negative regulators of Xoo resistance in rice. In addition, Os04g0301500 was involved in non-freezing temperatures (around 4°C) but not to 10°C cold stresses, suggesting a complex interplay with temperature signaling pathways. The study concludes that Os04g0301500 may play a crucial role in integrating biotic and abiotic stress responses in rice, potentially serving as a key regulator of plant resilience under changing environmental conditions, which could be important for further multiple stresses enhancement and molecular breeding through genetic engineering in rice.